A graphene oxide modified starch / chitosan composite packaging film and its preparation method and application
By using a one-step graft-modified graphene oxide dispersion in the starch/chitosan composite film, the problems of insufficient performance of starch-based films and poor compatibility of nanomaterials are solved, and uniform dispersion of ultra-low doping graphene oxide is achieved, which significantly improves the performance and cost-effectiveness of the film.
Patent Information
- Application Number
- CN202211462349.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-11-21
AI Technical Summary
The existing starch-based films have problems such as poor mechanical properties, low thermal stability, high sensitivity to humidity and prone to mildew in terms of performance. The introduced nanomaterials have poor compatibility and high cost, making it difficult to achieve practical application.
By adding graphene oxide dispersion to the carboxymethyl cellulose solution and one-step graft modification using urea under alkaline conditions, a uniform dispersion of modified graphene oxide was prepared, and then introduced into the starch/chitosan composite film was optimized to achieve uniform dispersion of ultra-low doping graphene oxide.
The ultra-low dosage of graphene oxide in the starch/chitosan composite film is achieved, which significantly improves the water resistance, mechanical properties and UV resistance of the film, reduces production costs, and extends the service life of the film.
Smart Images

Figure CN115850747B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional polymer materials, and specifically relates to a graphene oxide modified starch / chitosan composite packaging film and a preparation method and application thereof. Background Art
[0002] Pure starch films made from starch as the main raw material have many defects in performance, such as poor mechanical properties, low thermal stability, high sensitivity to humidity, and easy to mold, which makes them difficult to apply in actual production. At present, there is no pure starch film used for food packaging. In the modification research of starch-based films, the introduction of chitosan is a cost-effective modification scheme, which can improve the film-forming property, barrier property and mechanical properties of starch-based films, and can give the film a certain antibacterial ability, but it still cannot meet the actual daily use needs (Qian Qingyi, Li Chenchen, He Qingyun, Hu Suqing. Research and development of composite films based on soluble and edible chitosan starch [J]. Tianjin Science and Technology, 2022, 49(09): 60-63; Pei Nuo, Du Yufan, Sun Jie, Wang Zhihe. Effect of ultrasonic modification on the properties of chitosan / starch composite films [J]. Food and Fermentation Industries, 2022, 48(18): 88-94). Researchers have found that adding nanomaterials such as nano-silicon dioxide and nano-zinc oxide can significantly improve the performance of starch-based films. However, due to the poor compatibility of these nanomaterials with starch-based systems, the final modification effect is not ideal (Mao Wenying, Zhang Shuosheng, Du Junmin, Li Xia. Effect of Nano-SiO2 on the Properties of Starch / Chitosan Films [J]. Plastics, 2022, 51(03): 18-21; He Dong, Cheng Bo, Tang Ting. Preparation and Performance Study of ZnO / Chitosan / Starch Films [J]. Digital Printing, 2022, (02): 95-101.). In addition, the introduced nanomaterials generally have a high unit price and a large amount of addition, ranging from 1% to 5%, which greatly increases the preparation cost of nanomaterial-modified starch films, making it difficult to promote and apply.
[0003] Graphene oxide has attracted much attention due to its unique two-dimensional sheet structure, ultra-thin sheet thickness, ultra-large specific surface area, the presence of chemical groups such as carboxyl, hydroxyl, and epoxy on the sheet surface, and antibacterial properties. Introducing graphene oxide into starch-based films can significantly improve the performance of the films in various aspects. Related reports have suggested that the mass fraction of graphene oxide in starch-based films is between 0.1% and 2% to achieve the best performance of starch-based films (Li R, Liu C, Ma J. Studies on the properties of graphene oxide-reinforced starch biocomposites [J]. Carbohydrate Polymers, 2011, 84 (1): 631-637; Krystyjan M, Khachatryan G, Grabacka M, et al. Physicochemical, bacteriostatic, and biological properties of starch / chitosan polymer composites modified by graphene oxide, designed as new bionanomaterials [J]. Polymers, 2021, 13 (14): 2327.). Adopt the industrial grade graphene oxide with the lowest unit price on the market (unit price is about 20 yuan per gram), the lowest dosage of graphene oxide in the literature is 0.1% according to mass fraction, and cost estimation is carried out accordingly, and it is estimated that 100 grams of graphene oxide is contained in each ton of composite film, and the cost increased by adding graphene oxide is about 2000 yuan. The production cost is still high, which causes this starch-based film to be unable to enter production and practical application. Therefore, the cost of graphene oxide is the primary consideration when modifying starch-based film with graphene oxide, and the most direct way to reduce cost is to reduce the dosage. According to the size and specific surface area of graphene oxide nanosheets, it is believed that reducing the dosage of graphene oxide to 0.01% is fully able to meet the expected requirements through research. However, it is very difficult to reduce the dosage of graphene oxide from the current 0.1% to 0.01% level, and a creative dispersion method must be studied and sought. In (MaJ, Liu C, Li R, et al. Properties and structural characterization of oxidestarch / chitosan / graphene oxide biodegradable nanocomposites[J]. Journal of applied polymer science, 2012, 123(5): 2933-2944; -Doval R, - A, -Casarrubias EJ, et al. Physicochemical properties of pullulan / chitosan / graphene oxide composite films [J]. Polymer International, 2022, 71 (8): 959-965.) and other studies have shown that when the mass fraction is less than 0.1%, the properties of the film are significantly reduced and even fail to meet the application requirements. Because graphene oxide has a relatively strong intermolecular force in the solution, it is very easy to agglomerate, especially when the solution is alkaline or there are divalent or higher metal ions in the solution, the graphene oxide nanosheets are very easy to react with the metal ions to form a complex, thereby cross-linking the graphene oxide nanosheets, which greatly affects the dispersion effect of graphene oxide and the final performance of the material.
[0004] At present, the commonly used method for dispersing graphene oxide is ultrasonic dispersion and chemical modification of graphene oxide. Ultrasonic dispersion cannot overcome the strong intermolecular force between graphene oxide nanosheets to achieve uniform dispersion of a few sheets in the target product. The amount of graphene oxide added during ultrasonic dispersion must be greater than 0.1%, otherwise the effect and function of adding graphene oxide cannot be achieved. During chemical grafting modification, the performance of the selected chemical modification material and the chemical reaction of the modification will lead to different results. Improper selection will lead to a complex chemical modification process and higher cost, and will destroy the sheet structure of graphene oxide, so that the effect and function of graphene oxide are significantly reduced. For example, chloroacetic acid modification and polyol grafting modification are currently commonly used, which leads to multiple modification reaction processes, complex reactions, and poor dispersion and effect. Therefore, it is currently a challenging and creative task to prepare a uniform dispersion of graphene oxide with a few sheets by chemically modifying the dispersion of graphene oxide nanosheets and reduce its dosage to 0.01%. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a graphene oxide modified starch / chitosan composite packaging film and a preparation method and application thereof, so as to solve the problems of large graphene oxide dosage and uneven dispersion in the current preparation of starch-based films.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention discloses a method for preparing a graphene oxide modified starch / chitosan composite packaging film, which is characterized by comprising the following steps:
[0008] 1) adding graphene oxide dispersion to carboxymethyl cellulose solution, ultrasonically treating, adding urea, stirring evenly, adjusting the pH value to 9.0-9.5, heating to 70-80° C. for reaction for 2-3 hours, and then adjusting the pH value to 7.0-7.5 to obtain a modified graphene oxide few-layer uniform dispersion;
[0009] 2) adding polyvinyl pyrrolidone, chitosan solution and the modified graphene oxide few-layer uniform dispersion prepared in step 1) to the gelatinized starch solution, stirring at 70-80° C. for 30-50 minutes, casting, drying, cooling and taking out to obtain a graphene oxide modified starch / chitosan composite packaging film.
[0010] Optimally, in step 1), the mass ratio of carboxymethyl cellulose: graphene oxide dispersion: urea is (0.5-2): (40-60): (0.5-2).
[0011] Optimally, in step 2), the mass ratio of polyvinyl pyrrolidone: chitosan solution: modified graphene oxide few-layer uniform dispersion: gelatinized starch solution is (0.5-1): (3-5): (5-8): (5-8).
[0012] Optimally, in step 1), the graphene oxide dispersion is prepared by a modified Hummers method, the mass fraction of graphene oxide in the graphene oxide dispersion is 0.3% to 0.5%, the thickness of the graphene oxide nanosheet is 1.3 to 3.5 nm, the diameter is 150 to 530 nm, the pH value of the dispersion is 4 to 6, the mass fraction of oxygen in the graphene oxide is 31.6% to 33.7%, wherein the mass fraction of epoxy groups is 28.5% to 32.6%, the mass fraction of carboxyl groups is 38.3% to 42.4%, and the mass fraction of hydroxyl groups is 25.2% to 29.1%.
[0013] Optimally, in step 1), the modified graphene oxide dispersion can still maintain uniform and stable dispersion in an alkaline environment and in the presence of divalent calcium ions or trivalent aluminum ions.
[0014] Optimally, in step 1), the carboxymethyl cellulose solution is prepared by the following method:
[0015] In parts by mass, 140 to 155 parts of water are added to 0.5 to 2 parts of carboxymethyl cellulose, and the mixture is stirred at 25 to 30° C. for 2 to 3 hours to prepare a carboxymethyl cellulose solution.
[0016] Optimally, in step 2),
[0017] The chitosan solution is prepared by the following method:
[0018] In parts by mass, 3 to 5 parts of 99.5% glacial acetic acid are added to 85 to 95 parts of water, and 3 to 5 parts of 99.6% chitosan powder are slowly added at 35 to 45° C., and stirring is continued for 2 to 3 hours to obtain a chitosan solution;
[0019] The gelatinized starch solution is prepared by the following method:
[0020] By weight, 5 to 8 parts of starch and 90 to 100 parts of water are mixed evenly, and then 2 to 4 parts of 99% propylene glycol are added, and stirred at 80 to 90° C. for 30 to 50 minutes to prepare a gelatinized starch solution.
[0021] Optimally, in step 2), the drying condition is continuous drying at 45-55°C for 5-7 hours; the taking-out condition is cooling to 20-35°C and placing for 1-2 hours before taking out.
[0022] The invention also discloses a graphene oxide modified starch / chitosan composite packaging film prepared by the preparation method, which can block the passage of water vapor and air, shield 93.5-96.2% of ultraviolet rays, and the content of graphene oxide is only 0.008%-0.01% of the weight of the substrate.
[0023] The present invention also discloses the use of the graphene oxide modified starch / chitosan composite packaging film in the preparation of a starch-based film, which prolongs the service life of the film through contact antibacterial treatment.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention discloses a method for preparing a graphene oxide modified starch / chitosan composite packaging film. First, urea and carboxymethyl cellulose solution are used to complete the grafting modification with the carboxyl group in the graphene oxide dispersion under alkaline conditions through a one-step method, which has low cost, few chemical modification steps, high grafting efficiency, and a grafting efficiency of up to 95% to 98%. The product performance and structure are more stable because non-ionic hydroxyl groups, ether bonds and other hydrophilic groups are added to the graphene oxide structure. Second, compared with ordinary starch / chitosan films or composite films with uneven graphene oxide dispersion and large dosage, the graphene oxide modified starch / chitosan composite packaging film prepared in this application has strong water resistance, low water vapor permeability and good mechanical properties; it also has strong anti-ultraviolet ability, can shield 93.5% to 96.2% of the ultraviolet band, while maintaining a visible light transmittance of 42.9% to 50.3%, laying a foundation for practical application and promotion. Third, the carboxyl groups on carboxymethyl cellulose and the carboxyl groups on the graphene oxide structure form amide bonds under the action of the coupling agent urea to obtain a stable modified graphene oxide few-layer uniform dispersion, which reduces the carboxyl groups on the graphene oxide structure and avoids the carboxyl groups on the graphene oxide structure from easily forming complexes, ionic bonds and intermolecular forces with salt ions in the application environment under alkaline and acidic conditions. Fourth, the modified graphene oxide few-layer uniform dispersion is introduced into the starch / chitosan composite film system. Compared with the unmodified graphene oxide nanosheets, ultra-low doping modified graphene oxide nanosheets (mass fraction of about 0.01%) are achieved, and the effect of the modified starch / chitosan film is significantly improved. At the same time, by adding highly dispersed graphene oxide with nano effect, the internal structure of the film is optimized. By casting, the microstructure of the graphene oxide modified starch / chitosan composite packaging film is more compact.
[0026] Furthermore, by introducing a uniform dispersion of modified graphene oxide few sheets and optimizing the formula and process, the uniform dispersion of ultra-low-doped graphene oxide nanosheets in a few sheets in the modified starch / chitosan film was achieved, significantly reducing the additional cost of incorporating graphene oxide, and reducing the cost of incorporating graphene oxide from about 2,000 yuan to 200 yuan, a reduction of 90%.
[0027] The present invention also discloses a graphene oxide modified starch / chitosan composite packaging film prepared by the above-mentioned preparation method, wherein the graphene oxide nanosheet layer in the composite packaging film exhibits a significant nano effect, so that the performance of the composite packaging film is significantly improved; compared with starch / chitosan film or ordinary starch film, the mechanical properties of the graphene oxide modified starch / chitosan composite packaging film prepared by the method of the present invention are significantly improved, and the tensile strength thereof is increased by 17.8% to 23.4% and 94.2 to 103.5% compared with the control sample and the blank sample, respectively.
[0028] The present invention also discloses the use of the graphene oxide modified starch / chitosan composite packaging film prepared by the above preparation method in the preparation of starch-based films. The preparation cost is low and the service life of the film can be extended by contact antibacterial method. This performance has natural advantages over similar products when applied to industries such as food packaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The figure is a reaction mechanism diagram for preparing a uniform dispersion of modified graphene oxide with a few sheets disclosed in the present invention;
[0030] Figure 2 The present invention discloses a schematic diagram of the preparation process and microstructure of the graphene oxide modified starch / chitosan composite packaging film. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0032] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0033] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0034] Example 1
[0035] 1) adding 140 parts of water to 0.5 parts of carboxymethyl cellulose, stirring at 25° C. for 2 hours to prepare a carboxymethyl cellulose solution, adding 40 parts of graphene oxide dispersion, and ultrasonically treating for 15 minutes to obtain a graphene oxide / carboxymethyl cellulose composite dispersion;
[0036] 2) adding 0.5 parts of urea to the graphene oxide / carboxymethyl cellulose composite dispersion prepared in step 1) under stirring, adding 0.5 parts of 40% by mass sodium hydroxide solution to adjust the pH value of the system to 9.0 after the urea is dissolved, heating to 70° C. for reaction for 2 hours under stirring, and then adding 3 parts of 20% by mass citric acid solution to adjust the pH value of the system to 7.0 to obtain a modified graphene oxide few-layer uniform dispersion;
[0037] 3) adding 3 parts of 99.5% glacial acetic acid to 85 parts of water, slowly adding 3 parts of solid chitosan powder at 35° C. with stirring, and continuing stirring for 2 hours to obtain a chitosan solution;
[0038] 4) Mix 5 parts of corn starch and 90 parts of water, add 2 parts of glycerol, and stir at 80° C. for 30 minutes to prepare a gelatinized starch solution;
[0039] 5) adding 5 parts of the modified graphene oxide few-layer uniform dispersion prepared in step 2), the chitosan solution prepared in step 3) and 0.5 parts of polyvinyl pyrrolidone to the gelatinized starch solution prepared in step 4), stirring and reacting at 70° C. for 30 minutes to obtain an ultra-low-dosage graphene oxide modified starch / chitosan casting solution;
[0040] 6) The ultra-low-doped graphene oxide modified starch / chitosan casting solution prepared in step 5) is poured into a glass dish of the same size at the same weight, dried continuously at 45° C. for 6 hours, then cooled to 20° C. and left for 1 hour before being taken out to obtain a graphene oxide modified starch / chitosan composite packaging film.
[0041] The water vapor permeability coefficient of the graphene oxide modified starch / chitosan composite packaging film prepared in Example 1 is 0.91 g·cm / (cm 2 ·s·Pa), which was 40.9% and 64.5% lower than that of the control sample and the blank sample, respectively. The water contact angle was 126.6°, which was 19.5% and 87.6% higher than that of the control sample and the blank sample, respectively. The tensile strength was 68.7MPa, which was 20.1% and 98.0% higher than that of the control sample and the blank sample, respectively. The elongation at break was 1.62%, which was 47.3% and 42.1% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Escherichia coli was 52.7%±2.64%, which was 17.6% and 24.6% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Staphylococcus aureus was 49.82%±2.5%, which was 20.9% and 25.1% higher than that of the control sample and the blank sample, respectively. In the UV region, the ultraviolet shielding is 93.5%, which is 0.4% higher than the control sample and 156.9% higher than the blank sample; the visible light transmittance is 50%, which is 20.5% higher than the control sample and 44.6% lower than the blank sample.
[0042] Example 2
[0043] 1) adding 155 parts of water to 2 parts of carboxymethyl cellulose, stirring at 30° C. for 3 hours to prepare a carboxymethyl cellulose solution, adding 60 parts of graphene oxide dispersion, and ultrasonically treating for 30 minutes to obtain a graphene oxide / carboxymethyl cellulose composite dispersion;
[0044] 2) adding 2 parts of urea to the graphene oxide / carboxymethyl cellulose composite dispersion prepared in step 1) under stirring, adding 2 parts of 40% by mass sodium hydroxide solution to adjust the pH value of the system to 9.5 after the urea is dissolved, heating to 80° C. for reaction for 3 hours under stirring, and then adding 5 parts of 20% by mass citric acid solution to adjust the pH value of the system to 7.5 to obtain a modified graphene oxide few-layer uniform dispersion;
[0045] 3) adding 5 parts of 99.5% glacial acetic acid to 95 parts of water, slowly adding 5 parts of solid chitosan powder at 45° C. with stirring, and continuing stirring for 3 hours to obtain a chitosan solution;
[0046] 4) mixing 8 parts of corn starch and 100 parts of water, adding 4 parts of glycerol, and stirring at 90° C. for 50 minutes to prepare a gelatinized starch solution;
[0047] 5) adding 8 parts of the modified graphene oxide few-layer uniform dispersion prepared in step 2), the chitosan solution prepared in step 3) and 1 part of polyvinyl pyrrolidone to the gelatinized starch solution prepared in step 4), stirring and reacting at 80° C. for 50 minutes to obtain an ultra-low-dosage graphene oxide modified starch / chitosan casting solution;
[0048] 6) The ultra-low-doped graphene oxide modified starch / chitosan casting solution prepared in step 5) is poured into a glass dish of the same size at the same weight, dried continuously at 55° C. for 7 hours, then cooled to 35° C. and left for 2 hours before being taken out to obtain a graphene oxide modified starch / chitosan composite packaging film.
[0049] The water vapor permeability coefficient of the graphene oxide modified starch / chitosan composite packaging film prepared in Example 2 is 0.99 g·cm / (cm 2·s·Pa), which was 35.7% and 61.3% lower than that of the control sample and the blank sample, respectively. The water contact angle was 122.3°, which was 15.5% and 82.5% higher than that of the control sample and the blank sample, respectively. The tensile strength was 70.6MPa, which was 23.4% and 103.5% higher than that of the control sample and the blank sample, respectively. The elongation at break was 1.49%, which was 35.5% and 30.7% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Escherichia coli was 50.1%±2.51%, which was 11.8% and 18.4% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Staphylococcus aureus was 47.9%±2.40%, which was 16.3% and 20.4% higher than that of the control sample and the blank sample, respectively. In the UV region, the ultraviolet shielding rate is 96.2%, which is 3.3% higher than the control sample and 164.3% higher than the blank sample; the visible light transmittance is 47.5%, which is 14.5% higher than the control sample and 47.4% lower than the blank sample.
[0050] Example 3
[0051] 1) Add 150 parts of water to 1 part of carboxymethyl cellulose, stir at 25° C. for 2.5 hours to prepare a carboxymethyl cellulose solution, add 50 parts of graphene oxide dispersion, and ultrasonically treat for 20 minutes to obtain a graphene oxide / carboxymethyl cellulose composite dispersion.
[0052] 2) 1 part of urea is added to the graphene oxide / carboxymethyl cellulose composite dispersion prepared in step 1) under stirring, and after the urea is dissolved, 1.5 parts of a 40% by mass sodium hydroxide solution is added to adjust the pH value of the system to 9.0, and the mixture is heated to 80° C. and reacted for 2 hours under stirring, and then 4 parts of a 20% by mass citric acid solution are added to adjust the pH value of the system to 7.5 to obtain a modified graphene oxide few-layer uniform dispersion.
[0053] 3) adding 4 parts of 99.5% glacial acetic acid to 90 parts of water, slowly adding 4 parts of solid chitosan powder at 40° C. with stirring, and continuing stirring for 2.5 hours to obtain a chitosan solution;
[0054] 4) mixing 7 parts of corn starch and 95 parts of water, adding 3 parts of glycerol, and stirring at 85° C. for 40 minutes to prepare a gelatinized starch solution;
[0055] 5) adding 7 parts of the modified graphene oxide few-layer uniform dispersion prepared in step 2), the chitosan solution prepared in step 3) and 0.8 parts of polyvinyl pyrrolidone to the gelatinized starch solution prepared in step 4), stirring and reacting at 75° C. for 40 minutes to obtain an ultra-low-dosage graphene oxide modified starch / chitosan casting solution;
[0056] 6) The ultra-low-doped graphene oxide modified starch / chitosan casting solution prepared in step 5) is poured into a glass dish of the same size at the same weight, dried continuously at 50° C. for 6.5 hours, then cooled to 30° C. and left for 1.5 hours before being taken out to obtain a graphene oxide modified starch / chitosan composite packaging film.
[0057] The water vapor permeability coefficient of the graphene oxide modified starch / chitosan composite packaging film prepared in Example 3 is 1.02 g·cm / (cm 2 ·s·Pa), which was 33.8% and 39.8% lower than that of the control sample and the blank sample, respectively. The water contact angle was 117.4°, which was 10.9% and 75.2% higher than that of the control sample and the blank sample, respectively. The tensile strength was 67.3MPa, which was 17.8% and 94.2% higher than that of the control sample and the blank sample, respectively. The elongation at break was 1.51%, which was 32.3% and 32.5% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Escherichia coli was 53.5%±2.68%, which was 19.4% and 26.4% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Staphylococcus aureus was 50.03%±2.5%, which was 21.4% and 25.7% higher than that of the control sample and the blank sample, respectively. In the UV region, the ultraviolet shielding is 93.5%, which is 0.4% higher than the control sample and 156.9% higher than the blank sample; the visible light transmittance is 50%, which is 20.5% higher than the control sample and 44.6% lower than the blank sample.
[0058] Example 4
[0059] 1) adding 145 parts of water to 0.8 parts of carboxymethyl cellulose, stirring at 28° C. for 2.5 hours to prepare a carboxymethyl cellulose solution, adding 40 parts of graphene oxide dispersion, and ultrasonically treating for 25 minutes to obtain a graphene oxide / carboxymethyl cellulose composite dispersion;
[0060] 2) adding 0.9 parts of urea to the graphene oxide / carboxymethyl cellulose composite dispersion prepared in step 1) under stirring, adding 1.3 parts of 40% by mass sodium hydroxide solution to adjust the pH value of the system to 9.3 after the urea is dissolved, heating to 80° C. for reaction for 2 hours under stirring, and then adding 3.5 parts of 20% by mass citric acid solution to adjust the pH value of the system to 7.5 to obtain a modified graphene oxide few-layer uniform dispersion;
[0061] 3) adding 3.5 parts of 99.5% glacial acetic acid to 88 parts of water, slowly adding 3.5 parts of solid chitosan powder at 38° C. with stirring, and continuing stirring for 2.5 hours to obtain a chitosan solution;
[0062] 4) mixing 6 parts of potato starch and 96 parts of water, adding 2.5 parts of glycerol, and stirring at 86° C. for 35 minutes to prepare a gelatinized starch solution;
[0063] 5) adding 5 parts of the modified graphene oxide few-layer uniform dispersion prepared in step 2), the chitosan solution prepared in step 3) and 0.8 parts of polyvinyl pyrrolidone to the gelatinized starch solution prepared in step 4), stirring and reacting at 75° C. for 40 minutes to obtain an ultra-low-dosage graphene oxide modified starch / chitosan casting solution;
[0064] 6) The ultra-low-doped graphene oxide modified starch / chitosan casting solution prepared in step 5) is poured into a glass dish of the same size at the same weight, dried continuously at 48° C. for 6.5 hours, then cooled to 25° C. and left for 1.5 hours before being taken out to obtain a graphene oxide modified starch / chitosan composite packaging film.
[0065] The water vapor permeability coefficient is 0.94 g·cm / (cm 2 ·s·Pa), which was 40% and 63.3% lower than that of the control sample and the blank sample, respectively. The water contact angle was 123.8°, which was 16.9% and 84.8% higher than that of the control sample and the blank sample, respectively. The tensile strength was 69.3MPa, which was 21.2% and 99.7% higher than that of the control sample and the blank sample, respectively. The elongation at break was 1.55%, which was 40.9% and 36% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Escherichia coli was 50.3%±2.52%, which was 12.3% and 18.9% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Staphylococcus aureus was 45.6%±2.28%, which was 10.7% and 14.6% higher than that of the control sample and the blank sample, respectively. In the UV region, the ultraviolet shielding was 94.7%, which was 1.7% higher than that of the control sample and 160.2% higher than that of the blank sample; the visible light transmittance was 45.2%, which was 8.9% higher than that of the control sample and 49.9% lower than that of the blank sample.
[0066] Example 5
[0067] 1) adding 150 parts of water to 1.8 parts of carboxymethyl cellulose, stirring at 30° C. for 3 hours to prepare a carboxymethyl cellulose solution, adding 40 parts of graphene oxide dispersion, and ultrasonically treating for 28 minutes to obtain a graphene oxide / carboxymethyl cellulose composite dispersion;
[0068] 2) 1.6 parts of urea are added to the graphene oxide / carboxymethyl cellulose composite dispersion prepared in step 1) under stirring, and after the urea is dissolved, 1.3 parts of a 40% by mass sodium hydroxide solution are added to adjust the pH value of the system to 9.2, and the mixture is heated to 75° C. and reacted for 3 hours under stirring, and then 3 parts of a 20% by mass citric acid solution are added to adjust the pH value of the system to 7.5 to obtain a modified graphene oxide few-layer uniform dispersion;
[0069] 3) adding 4 parts of 99.5% glacial acetic acid to 95 parts of water, slowly adding 4.5 parts of solid chitosan powder at 45° C. with stirring, and continuing stirring for 3 hours to obtain a chitosan solution;
[0070] 4) 8 parts of sweet potato starch and 95 parts of water were mixed, 3.5 parts of glycerol were added, and the mixture was stirred at 90° C. for 45 minutes to prepare a gelatinized starch solution;
[0071] 5) adding 7.5 parts of the modified graphene oxide few-layer uniform dispersion prepared in step 2), the chitosan solution prepared in step 3) and 0.7 parts of polyvinyl pyrrolidone to the gelatinized starch solution prepared in step 4), stirring and reacting at 80° C. for 45 minutes to obtain an ultra-low-dosage graphene oxide modified starch / chitosan casting solution;
[0072] 6) The ultra-low-doped graphene oxide modified starch / chitosan casting solution prepared in step 5) is poured into a glass dish of the same size at the same weight, dried continuously at 55° C. for 7 hours, then cooled to 30° C. and left for 2 hours before being taken out to obtain a graphene oxide modified starch / chitosan composite packaging film.
[0073] The water vapor permeability coefficient is 0.97 g·cm / (cm 2 ·s·Pa), which was 37% and 62.1% lower than that of the control sample and the blank sample, respectively. The water contact angle was 121.4°, which was 14.6% and 81.2% higher than that of the control sample and the blank sample, respectively. The tensile strength was 67.5MPa, which was 18.0% and 94.5% higher than that of the control sample and the blank sample, respectively. The elongation at break was 1.59%, which was 44.5% and 39.5% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Escherichia coli was 50.6%±2.5%, which was 12.9% and 19.6% higher than that of the control sample and the blank sample, respectively. The antibacterial rate of Staphylococcus aureus was 46.2%±2.3%, which was 12.1% and 16.1% higher than that of the control sample and the blank sample, respectively. In the UV region, the ultraviolet shielding was 94.2%, which was 1.2% higher than that of the control sample and 158.8% higher than that of the blank sample; the visible light transmittance was 46.7%, which was 12.5% higher than that of the control sample and 48.3% lower than that of the blank sample.
[0074] Control samples
[0075] The control sample is a starch film without modified graphene oxide, and the modified graphene oxide is replaced by unmodified graphene oxide with the same concentration. The synthesis process conditions and methods are the same as those of the present invention. The water vapor permeability coefficient of the starch film of the control sample is 1.54 g·cm / (cm 2·s·Pa), water contact angle is 105.9°, tensile strength is 57.2MPa, elongation at break is 1.1%, Escherichia coli antibacterial rate is 44.8±2.24%, Staphylococcus aureus antibacterial rate is 41.2±2.06%, UV shielding in the UV region is 93.1%, and visible light transmittance is 41.5%.
[0076] Blank Sample
[0077] The blank sample is a starch film without graphene oxide and modified graphene oxide, and the synthesis process conditions and methods are the same as those of the present invention. The water vapor permeability coefficient of the control sample starch film is 2.56 g·cm / (cm 2 ·s·Pa), the water contact angle is 67°, the tensile strength is 34.7MPa, the elongation at break is 1.14%, the antibacterial rate of Escherichia coli is 42.3±2.12%, the antibacterial rate of Staphylococcus aureus is 39.8±1.99%, the shielding efficiency in the ultraviolet region is 36.4%, and the visible light transmittance is 90.3%.
[0078] The degree of substitution of carboxymethyl cellulose selected in the preparation process is 0.9, and the viscosity is 800-1200 mPa·s; the degree of deacetylation of chitosan is 80-95%; glacial acetic acid, glycerol and polyvinyl pyrrolidone are all of chemically pure grade; the starch is corn starch, which contains about 73% amylopectin and 27% amylose, corresponding to an amylopectin / amylose ratio of 2.7 (weight average molecular weight of 9.8×10 7 g / mol, number average molecular weight is 5.9×10 7 The prepared modified graphene oxide dispersion can still maintain uniform and stable dispersion in an alkaline environment (using a sodium hydroxide solution to adjust the solution pH to above 12) and in the presence of divalent calcium ions (saturated calcium hydroxide solution) and trivalent aluminum ions (aluminum chloride).
[0079] See also Figure 1 The diagram is a reaction mechanism diagram for preparing a uniform dispersion of modified graphene oxide few sheets disclosed in the present invention. Figure 1 The figure shows a schematic diagram of the chemical reaction for preparing carboxymethyl cellulose modified graphene oxide by a one-step method. Urea and carboxymethyl cellulose solution are grafted with graphene oxide under alkaline conditions in a one-step method. Urea, as a coupling agent, undergoes an amidation reaction with the carboxyl groups in carboxymethyl cellulose and the carboxyl groups on graphene oxide at the same time. The reaction results in the grafting of cellulose containing multiple hydroxyl groups on the graphene oxide nanosheet layer in the form of an amide bond, thereby improving the stability of graphene oxide in different environments. At the same time, the unreacted carboxyl groups in the graphene oxide structure can also form hydrogen bonds with the carboxyl groups in carboxymethyl cellulose to improve the stability of the graphene oxide dispersion. The one-step method completes the grafting modification, with low cost, fewer chemical modification steps, high grafting efficiency, and more stable product performance and structure.
[0080] See also Figure 2 The present invention discloses a schematic diagram of the preparation process and microstructure of the graphene oxide modified starch / chitosan composite packaging film. As can be seen from the figure, graphene oxide is evenly dispersed in the modified starch / chitosan composite film in the form of a few layers.
[0081] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a graphene oxide modified starch / chitosan composite packaging film, characterized in that: The following steps are involved: 1) Add graphene oxide dispersion to carboxymethyl cellulose solution, add urea after ultrasonic treatment, stir evenly, adjust pH value to 9.0-9.5, heat to 70-80 °C and react for 2-3 hours, then adjust pH value to 7.0-7.5 to obtain modified graphene oxide few-sheet uniform dispersion; 2) adding polyvinyl pyrrolidone, chitosan solution and the modified graphene oxide few-layer uniform dispersion prepared in step 1) to the gelatinized starch solution, stirring at 70-80° C. for 30-50 minutes, casting, drying, cooling and taking out to obtain a graphene oxide modified starch / chitosan composite packaging film; In step 1), the mass ratio of carboxymethyl cellulose: graphene oxide dispersion: urea is (0.5-2): (40-60): (0.5-2); The mass fraction of graphene oxide in the graphene oxide dispersion is 0.3%~0.5%.
2. The method for preparing the graphene oxide modified starch / chitosan composite packaging film according to claim 1, characterized in that: In step 2), the mass ratio of polyvinyl pyrrolidone:chitosan solution:modified graphene oxide few-layer uniform dispersion:gelatinized starch solution is (0.5-1):(3-5):(5-8):(5-8).
3. The method for preparing the graphene oxide modified starch / chitosan composite packaging film according to claim 1, characterized in that: In step 1), the graphene oxide dispersion is prepared by a modified Hummers method, the graphene oxide nanosheet layer has a thickness of 1.3-3.5 nm, a diameter of 150-530 nm, a pH value of the dispersion of 4-6, and a mass fraction of oxygen in the graphene oxide of 31.6%-33.7%, wherein the mass fraction of epoxy groups is 28.5%-32.6%, the mass fraction of carboxyl groups is 38.3%-42.4%, and the mass fraction of hydroxyl groups is 25.2%-29.1%.
4. The method for preparing the graphene oxide modified starch / chitosan composite packaging film according to claim 1, characterized in that: In step 1), the carboxymethyl cellulose solution is prepared by the following method: In parts by mass, 140-155 parts of water are added to 0.5-2 parts of carboxymethyl cellulose, and the mixture is stirred at 25-30° C. for 2-3 hours to prepare a carboxymethyl cellulose solution.
5. The method for preparing the graphene oxide modified starch / chitosan composite packaging film according to claim 1, characterized in that: In step 2), The chitosan solution is prepared by the following method: In parts by mass, 3 to 5 parts of 99.5% glacial acetic acid are added to 85 to 95 parts of water, and 3 to 5 parts of 99.6% chitosan powder are slowly added at 35 to 45° C., and stirring is continued for 2 to 3 hours to obtain a chitosan solution.
6. The method for preparing the graphene oxide modified starch / chitosan composite packaging film according to claim 1, characterized in that: In step 2), The gelatinized starch solution is prepared by the following method: By weight, 5 to 8 parts of starch and 90 to 100 parts of water are uniformly mixed, and then 2 to 4 parts of 99% by weight propylene glycol are added, and stirred at 80 to 90° C. for 30 to 50 minutes to prepare a gelatinized starch solution.
7. The method for preparing the graphene oxide modified starch / chitosan composite packaging film according to claim 1, characterized in that: In step 2), the drying condition is continuous drying at 45-55°C for 5-7 hours; the removal condition is cooling to 20-35°C and placing for 1-2 hours before removal.
8. A graphene oxide modified starch / chitosan composite packaging film prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The content of graphene oxide is 0.008%~0.01% of the weight of the substrate.